Ansambel Musik Nggo Lamba Dalam Upacara Pati Ka Du’a Bapu Ata Mata Di Danau Kelimutu Ende Flores Nusa Tenggara Timur - Ariesty Victoria Kartina (SELONDING, 2017)
Performance of art in a community is a part from community culture it self. Community  as the owner of culture has a role to preserve it. Performance of art has different  shape from each other. Performance of art it self has a special meaning and this is corresponding with it’s context. Nggo Lamba music performancein Lio Ende Flores East Nusa Tenggara is a folk performing arts that’s used to accompany custom dance at many kinds of custom ceremony like thanksgiving ceremony, wedding ceremony, Pati Ka ceremonyand etc.  This writing is a discription of the series  process of a Pati Ka ceremonies at Kelimutu lake from preparing until peak of the event ceremonies.Keywords: Nggo Lamba, Pati Ka Du’a Bapu Ata Mata.